The contributions of university chaplains, as spiritual care professionals, to suicide prevention: results from a European expert panel - Saliba, Serena Margaret (Journal of spirituality in mental health, 2025)
University chaplains are responsible for providing spiritual care to all members of the university community. Within the multifaceted duties of a university chaplain, one crucial (yet often overlooked) aspect is suicide prevention. To identify the contributions of university chaplains to suicide prevention, seven university chaplains located in four European countries participated in three focus group sessions. Two overarching themes were generated from the focus group sessions: key elements of university chaplaincy; and the contributions of university chaplains to suicide prevention. The study revealed that university chaplains contribute to all three phases of suicide prevention: prevention, intervention, and postvention.